2019
DOI: 10.1080/19419899.2019.1684354
|View full text |Cite
|
Sign up to set email alerts
|

Use of ‘gay dating apps’ and its relationship with individual well-being and sense of community in men who have sex with men

Abstract: Use of 'gay dating apps' by men who have sex with men Abstract There is growing literature and empirical work that is investigating if and how mobile phone and tablet dating apps are influencing the lives of their users. An online questionnaire-based study was developed to investigate how men who have sex with men (MSM) use 'gay dating apps' (GDAs), and how such use may relate to different aspects of their lives on an individual and on a collective level. The study included data from 191 MSM living in the UK w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 63 publications
3
41
1
Order By: Relevance
“…This block can also include studies on the problematic use of apps, which can affect the daily lives of users [ 34 , 56 ], and research that focuses on the possible negative psychological effects of their use, as a link has been shown between using dating apps and loneliness, dissatisfaction with life, and feeling excluded from the world [ 24 , 34 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…This block can also include studies on the problematic use of apps, which can affect the daily lives of users [ 34 , 56 ], and research that focuses on the possible negative psychological effects of their use, as a link has been shown between using dating apps and loneliness, dissatisfaction with life, and feeling excluded from the world [ 24 , 34 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Available data on mental health primarily describe the prevalence of mental disorders (depression, anxiety, personality disorders) among MSM. In short, these data show that, compared with non-users, MSM using DAs report lower perception of community belonging, higher isolation, less satisfaction with life, and worse quality of sleep (2,21). The stigma and discrimination experienced by the MSM community may be a possible explanation for the more frequent recreational drug use in this group than in the general population.…”
Section: Discussionmentioning
confidence: 79%
“…Duncan et al (21) found that MSM app users reported low sleep quality (34.6% of respondents) and short sleep duration (43.6% of respondents), which were linked to depressive symptoms, engaging in unprotected anal sex, as well as alcohol and drug use. Moreover, loneliness seemed to be negatively correlated with sharing private information through gay DAs (2). In contrast, a positive impact on sexual self-acceptance could be observed in the LGBT group of people who were digitally connecting to each other (22).…”
Section: Characteristics and Mental Health Of Msm Who Use Mobile Dasmentioning
confidence: 88%
See 1 more Smart Citation
“…These results may support the “loneliness hypothesis” as a common underlying factor between smoking and dating app use. Several studies showed the role of individual loneliness in the motives for dating app use [ 56 , 57 , 58 ]: people who use the apps searching for new people to meet may actively install them as a strategy to reduce social isolation or a way to cope with social anxiety. Therefore, dating app use and cigarette smoking might be parallel strategies to cope with feelings of loneliness or social anxiety.…”
Section: Discussionmentioning
confidence: 99%